Competing Logics in the Further Standardization of Fair Trade: ISEAL and the Símbolo de Pequeños Productores - Renard , Marie-Christine; Loconto, Allison (The International Journal of Sociology of Agriculture and Food, 2013)
In light of the rise of the (semi-)private regulation of markets through standards systems, this article explores the underlying processes by which private governance is developed through two case studies of fair trade. We illustrate howthere are competing logics playing out in different parts of the movement with regards to how the core values that the system is supposed to promote (i.e. fairness and smallholder empowerment) are being defined. We show that participation, as a core type of input legitimacy, is still highly contested even when it is present. Moreover, there is an intricate relationship between the tools of governance and participation. We argue that the focus on the tools is currently overriding the values of fairness on which they are supposed to deliver. We therefore propose that attention be paid to how these tools are used and by whom, so to value which aspects of fair trade.